Pengaruh Work-Life Balance Terhadap Kepuasan Kerja Karyawan Telkom Property Wilayah Bengkulu - Septiara, Jeny; Al Hidayat, Rahmat; Charolina, Ovita (Jurnal Administrasi Bisnis Nusantara, 2026)
This study aims to determine and analyze the Effect of Work-Life Balance on Job Satisfaction of TelkomProperty Employees in the Bengkulu Region. The type of research used in this study is a quantitative approach. The population in this study were all TelkomProperty Employees in the Bengkulu Region. The sample used in this study was 80 respondents using total sampling and data analysis techniques. The data analysis technique used to test the hypothesis was a simple linear regression analysis and t-test (partial test) which was processed using statistical calculations through the Statistical for the Social Science (SPSS) version 25 application. The results of this study indicate that Work-Life Balance has a positive and significant effect on Job Satisfaction of TelkomProperty Employees in the Bengkulu Region as evidenced by the Work-Life Balance regression coefficient value (X) of 0.674 and a calculated t value of 7.561> t table 1.990 with a significant value of 0.000 <0.05.